2021
DOI: 10.3389/fonc.2021.726745
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Mesenchymal-Related Long Non-Coding RNA Prognostic Model in Glioma

Abstract: Glioma is well known as the most aggressive and prevalent primary malignant tumor in the central nervous system. Molecular subtypes and prognosis biomarkers remain a promising research area of gliomas. Notably, the aberrant expression of mesenchymal (MES) subtype related long non-coding RNAs (lncRNAs) is significantly associated with the prognosis of glioma patients. In this study, MES-related genes were obtained from The Cancer Genome Atlas (TCGA) and the Ivy Glioblastoma Atlas Project (Ivy GAP) data sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In pathologic analysis, we found that HGGs had higher KDELR1 expression than LGGs. In addition, previous studies (35)(36)(37) have demonstrated that mesenchymal-subtype gliomas are associated with poor prognosis, which are confirmed by our finding that mesenchymal -subtype gliomas had a higher expression level of KDELR1 than proneural subtype gliomas. Subsequently, we further explored whether the expression of KDELR1 is related to recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…In pathologic analysis, we found that HGGs had higher KDELR1 expression than LGGs. In addition, previous studies (35)(36)(37) have demonstrated that mesenchymal-subtype gliomas are associated with poor prognosis, which are confirmed by our finding that mesenchymal -subtype gliomas had a higher expression level of KDELR1 than proneural subtype gliomas. Subsequently, we further explored whether the expression of KDELR1 is related to recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Through high-throughput bioinformatics analysis, many studies have shown that AL031985.3 is associated with the prognosis of HCC and can be used to build a predictive model for the prognosis of HCC [42][43][44]. Previous studies have found that SNHG18 is abnormally expressed in glioma tissue specimens, and high expression of SNHG18 in gliomas enhances their radiation resistance [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA SNHG18 has been identified as a novel prognostic biomarker for tumours in previous studies, and high SNHG18 expression is correlated with a poor prognosis. For example, SNHG18 knockdown suppressed metastasis and invasion of gliomas ( Huang et al, 2021 ). Furthermore, mkl1-induced SNHG18 regulates the metastasis and growth of non-small cell lung cancer by modulating the miR-211-5p/BRD4 pathway ( Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%